2020
DOI: 10.1037/xge0000703
|View full text |Cite
|
Sign up to set email alerts
|

A systematic investigation of conceptual color associations.

Abstract: A systematic investigation of conceptual colour associations. Associations with colours are a rich source of meaning and there has been considerable interest in understanding the capacity of colour to shape our functioning and behaviour as a result of colour associations. However, abstract conceptual colour associations have not been comprehensively investigated and many of the effects of colour on psychological functioning reported in the literature are therefore reliant on ad hoc rationalisations of conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 82 publications
(149 reference statements)
0
44
0
Order By: Relevance
“…Both results of this research and literature on the color‐emotion association and color perception of blue were mostly positive. In this positive result, the positive aspects of purple tended to be mainly associated with feminity, regal, 63 children, and laughing 41 . For green color, while the color‐emotion association results of this research were compatible with the results of the literature research, color perception results were not compatible with each other.…”
Section: Discussionmentioning
confidence: 80%
“…Both results of this research and literature on the color‐emotion association and color perception of blue were mostly positive. In this positive result, the positive aspects of purple tended to be mainly associated with feminity, regal, 63 children, and laughing 41 . For green color, while the color‐emotion association results of this research were compatible with the results of the literature research, color perception results were not compatible with each other.…”
Section: Discussionmentioning
confidence: 80%
“…In the inter-country gender-stratified comparison, findings regarding the color association with energy drinks were as follows: The result for Q1 suggests that eye-catching colors in the energy drinks section are mainly red and yellow, regardless of country. Color psychology research has suggested that different colors have different effects on the psychology and behaviors of humans; for example, red increases attention and aggressiveness while blue increases subjective alertness [ 23 , 24 ]. It is noteworthy that some associations between color and psychology are limited to specific populations; for example, red was associated with enthusiasm only in a Chinese population [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Color psychology research has suggested that different colors have different effects on the psychology and behaviors of humans; for example, red increases attention and aggressiveness while blue increases subjective alertness [ 23 , 24 ]. It is noteworthy that some associations between color and psychology are limited to specific populations; for example, red was associated with enthusiasm only in a Chinese population [ 24 ]. Energy drink distributors might consider that red and yellow are appropriate colors for energy drinks to attract the attention of both Taiwanese and Japanese consumers.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) found that in China, red is associated with marriage and luck, whereas in the UK, luck is instead associated with the color green. Tham et al. (2020) also found that Chinese, but not English participants, associated the color purple with mysterious .…”
Section: Potential Effects Of Culture On Perception Of the Dress And The Jacketmentioning
confidence: 94%
“…In general, people tend to associate colors with different concepts and emotions (Chen et al., 2020). Many color associations are consistent across cultures (Tham et al., 2020), especially color-emotion associations (Adams & Osgood, 1973; Hupka et al., 1997; Jonauskaite, Abu-Akel, et al., 2020). For instance, anger is associated with red, and fear is associated with black across cultures (Hupka et al., 1997).…”
Section: Potential Effects Of Culture On Perception Of the Dress And The Jacketmentioning
confidence: 99%